PENYEBAB KEMATIAN IBU DI KABUPATEN KULON PROGO YOGYAKARTA - Kurniati, Ana; Djanah, Nur (Poltekkes Kemenkes Yogyakarta, 2015)
Indonesia's maternal mortality was about 246/100,000 live births in 2007. It was still far from the target of achieving the MDG ?sin2015 that is 125/100,000 live births. Data were obtained from Kulon Progo's Health Department of Family Health Section. It wasfound that maternal mortality in Kulon Progo was rising, although it was still below from the figure of Yogyakarta Province, namely70/100,000 live births in 2010, and it was increased again to 132/100,000 live births in 2013. The aimed of this study was to describethematernalmortality that occurred inKulon Progo regency ranging fromyears 2009 -2013.This study was using descriptive study with cross sectional, it was conducted in Kulon Progo Regency Health Office. The subjectswerewomen who died during pregnancy until 42 days after giving birth regions in Kulon Progo in the years 2009-2013. The collectionof data were obtained from the Perinatal Maternal Audit report. This study was using descriptive analysis of the data revealed.During the years of 2009-2013 there were 30 cases of maternal mortality in Kulon Progo. The most direct obstetric causes ofmaternal death were obtained preeclampsia / eclampsia (23.34%), and than infection (16.67%), amniotic fluid embolism(6.67%),atonic (6.67%) and bleeding (3.33%). Most obstetric complications was not directly caused by heart disease (20 %). Based on thematernal reproductive factors,most maternal died on healthy reproductive age (20-30 years) asmuch as 66.67%and the risk parity(1 and > 3) as much as 70%, themajority ofmothers basic education (elementary /junior high school equivalent).Mostmaternal diedin health facilities and largely attended by health workers is 96.67 %. Most maternal mortality were occurred in health facilities,assisted by skilled health personnel,mostly routine antenatal care, died at the age of 20-30 yearswith parity 1 or >3, most maternalmortality with basic education, and poor families, most of them have a history of illness. The main cause were preeclampsia /eclampsia and heartdisease.